2022
DOI: 10.1111/jfs.12984
|View full text |Cite
|
Sign up to set email alerts
|

Possible explanation for limited reduction of pathogens on radish microgreens after spray application of chlorinated water during growth with disperse contamination spread of abiotic surrogate on leaves

Abstract: The purpose of this study was to determine the efficacy of spray application of chlorinated water before harvest on the population of Salmonella enterica Typhimurium and Escherichia coli O157:H7 on radish microgreens. The transfer of abiotic surrogate to radish microgreens was also evaluated to track possible pathogen contamination spread by inoculating seed and growth media. During growth, microgreens inoculated with strains of pathogens were sprayed with chlorinated water at three different concentrations (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…These authors also observed that washing with ethanol following treatment with citric acid was a successful alternative to chlorinated water, as it showed similar/equivalent effects to that of chlorinated treatment during the storage period. Spraying with chlorinated water during the growth of radish microgreens has been reported to reduce populations of Salmonella and Escherichia coli O157/H7 up to 1.1 and 0.9 log CFU/g, respectively …”
Section: Postharvest Technology and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also observed that washing with ethanol following treatment with citric acid was a successful alternative to chlorinated water, as it showed similar/equivalent effects to that of chlorinated treatment during the storage period. Spraying with chlorinated water during the growth of radish microgreens has been reported to reduce populations of Salmonella and Escherichia coli O157/H7 up to 1.1 and 0.9 log CFU/g, respectively …”
Section: Postharvest Technology and Qualitymentioning
confidence: 99%
“…Spraying with chlorinated water during the growth of radish microgreens has been reported to reduce populations of Salmonella and Escherichia coli O157/H7 up to 1.1 and 0.9 log CFU/g, respectively. 109 Various preservation techniques have been developed and tested by different researchers to extend the shelf life of vegetables. Nevertheless, a study on the postharvest technologies of BM is needed as only a relatively small number of studies have been conducted until now.…”
Section: Postharvest Technology and Qualitymentioning
confidence: 99%
“…The agar−agar is mixed with the water, and mixtures of agar−agar + water are sprinkled on seed material containing growth media. 143,144 145 The harvesting period is 2−4 days for rice grass, 146 6−9 days for barley grass, 6−9 days for wheat grass, 147 6−9 days for oat grass, 148 8−12 days for jowar grass, 149 7 days for maize grass, 150 7−14 days for buckwheat, 151 4−6 days for mung bean, 152 6−8 days for chickpea, 153 12−14 days for mint, 154 20 days for basil, 155 18−20 days for sage, 156 16−22 days for oregano, 157 9−12 days for amaranth, 158 10−12 days for beet, 159 8−12 days for chard, 160 12−21 days for red swiss chard, 161 10−17 days for quinoa, 162 4−6 days for spinach, 163 14−25 days for chives, 164 12−14 days for garlic, 165 10−12 days for leeks, 166 12 days for onion, 167 15−25 days for carrot, 168 7− 21 days for dill, 169 21−30 days for celery, 170 10−14 days for fennel, 171 5−10 days for radish, 172 5−20 days for aster cress, 173 8−16 days for mustard, 174 7−12 days for sunflower, 175 7−21 days for linseed, 176 7−21 days for cucumber, 4−20 days for Jute, 177 7−21 days for squash, 178 7−14 days for chicory, 179 8− 16 days for endive, 180 7−16 days for lettuce, 181 7−21 days for beans, <...…”
Section: Microgreen Plant Production In Soilless Culturementioning
confidence: 99%
“…Mikroyeşillikler: besinsel içeriği, sağlık üzerine etkisi, üretimi ve gıda güvenliği. GIDA (2022) 47 (4) 630-649 doi: 10.15237/ gida.GD22041 Işık, S., Işık, H., Zytemiş, Z., Güner, S., Aksoy, A., Çetin, B., Topalcengiz, Z. (2022).…”
unclassified
“…Microgreens: nutritional content, health effect, production, and food safety. GIDA (2022) 47 ( 4) 630-649 doi: 10.15237/ gida.GD22041 ÖZ Günümüzde sağlıklı ve organik gıdalara olan talep giderek artmaktadır. Bu gıdalardan biri olan mikroyeşillikler; sahip oldukları canlı renk, hassas yapı, yüksek aroma ve özellikle içerdikleri biyoaktif bileşenlerden dolayı sağlık üzerinde olumlu etkileri nedeniyle son yıllarda tüketicilerin ilgisini çekmektedir.…”
unclassified